DINAMIKA EMOSI DAN STRATEGI MANAJEMEN KONFLIK PADA REMAJA DI LEMBAGA PEMBINAAN KHUSUS ANAK: EMOTIONAL DYNAMICS AND CONFLICT MANAGEMENT STRATEGIES AMONG ADOLESCENTS IN JUVENILE CORRECTIONAL INSTITUTIONS - Sirri Nahzatun Qowimah; Angellina Anastasia Halim; Mary Philia Elisabeth; Jefri Setyawan (Jurnal Pengabdian Masyarakat Multidisiplin, 2026)
Adolescents undergoing rehabilitation in Juvenile Correctional Institutions (Lembaga Pembinaan Khusus Anak [LPKA]) face complex emotional and social conflicts due to their history of legal violations, environmental stressors, and separation from family. Inability to manage emotions and conflicts can hinder the rehabilitation process and increase the risk of maladaptive behaviors. This study aims to explore the emotional dynamics and conflict management strategies of adolescents in LPKA Blitar. Using a descriptive qualitative approach and thematic analysis, data were collected through in-depth interviews, participatory observations, and a series of emotion-based intervention activities. The interventions involved conflict simulation exercises, 4-7-8 breathing techniques, symbolic reflection using visual media such as the "Emotion Jar," and written self-commitments. The results indicate that adolescents’ conflicts were complex, encompassing both interpersonal and intrapersonal dimensions, which were characterized by emotions such as anger, regret, disappointment, and fear. Initial responses tended to be maladaptive, including verbal aggression, throwing objects, and withdrawal. After the intervention, adolescents began to restrain their impulses and express discomfort verbally. The 4-7-8 breathing technique and the “Emotion Jar” helped adolescents manage and release their emotions constructively. These findings highlight the importance of conflict management approaches that strengthen emotional regulation and incorporate positive psychology values in adolescent rehabilitation. The study has implications for the development of contextual and sustainable psychosocial programs in LPKA and similar institutions to support long-term behavioral transformation.